The "What" and "Hows" of Mindfulness: Using DBT's Mindfulness Skills to Reduce Test Anxiety - John E. Lothes II; Kirk Mochrie (The Ohio State University Libraries, 2017)
Background: Many studies have shown the positive effects of extended mindfulness interventions on anxiety reduction in several different populations; however, few have yet to examine the effects of mindfulness interventions on test anxiety in a college student population. Aim: This study assesses the effects of overall test anxiety reduction through the use of Dialectical Behavior Therapy's (DBT's) mindfulness skills over an eight-week period among college students. Methods: Participants included 16 college students that were trained in mindfulness, which included an eight-week mindfulness training using DBT's "What" and "How" skills of the mindfulness module. Participants were assessed on text anxiety, general anxiety, and mindfulness at the beginning, mid-way point, and end of the study. A weekly schedule of mindfulness practices was given to participants to complete on their own at home. Results: Participants showed significant within-group reductions in test anxiety from the start of the study (Mean = 56, SD = 11.47) to the end of the study (Mean = 37.56, SD = 9.98). Conclusions: It is likely a mindfulness intervention that specifically teaches the "What" and "How" skills of DBT can help students reduce not only test anxiety, but overall anxiety, as well as increase individual levels of mindfulness based on the self-reported mindfulness questionnaire. Further research is needed to more definitively assess these results matched against a wait-list control group.